Phasing out of the apparel quota : addressing livelihood concerns in Bangladesh. - Centre for Policy Dialogue (Bangladesh) (Dhaka : University Press, 2003)
Report on the ready made garment industry of Bangladesh primarily meant for export markets; includes articles on the socio-economic conditions of the workers of this industry.
"A strategy paper prepared by the Centre for Policy Dialogue (CPD) in connection with the global trade campaign by the Oxfam International."
Keywords: Clothing trade -- Bangladesh; Clothing workers -- Bangladesh -- Social conditions -- 20th century; Clothing workers -- Bangladesh -- Economic conditions -- 20th century; Export marketing -- Bangladesh